Pelanggaran Penelitian Ilmiah Kelautan Tanpa Izin oleh Pihak Asing di Wilayah Indonesia - Lapadengan, M. Ikhsan; Afriansyah, Arie (Faculty of Law, Universitas Jambi, 2023)
Scientific understanding of the sea is very important for human activities on the marine environment and the biota contained therein in order to maintain marine ecosystems. It affects the marine environment and the biota contained therein. Marine scientific research refers to various disciplines, such as biology, biotechnology, geology, chemistry, physics, geophysics, hydrography, physical oceanography, and marine drilling. Nevertheless, it is necessary to regulate marine scientific research, both from international law and national law of coastal countries. Indonesia as a member of the 1982 UN Convention on the Law of the Sea, has the authority to regulate and enforce the law on marine scientific research in the jurisdiction of its country. This article will be talk about how Indonesia, as a sovereign country, regulates the jurisdiction of its country, in terms of marine scientific research, as well as how Indonesia's efforts to enforce the law against foreign parties who carry out marine scientific research in its territory. Enforcement of this law will have a major impact on the security of sovereignty and the advancement of science and technology in the marine sector for Indonesia.